Rheological Impact of GBT1118 Cessation in a Sickle Mouse Model - Kanne, Celeste K.; Nebor, Danitza; Pochron, Mira; Oksenberg, Donna; Sheehan, Vivien A. (Frontiers in Physiology, 2021)
In sickle cell disease, higher whole blood viscosity is a risk factor for vaso-occlusive crisis, avascular necrosis, and proliferative retinopathy. Blood viscosity is strongly impacted by hemoglobin (Hb) levels and red blood cell (RBC) deformability. Voxelotor is a HbS polymerization inhibitor with anti-sickling properties that increases the Hb affinity for oxygen, thereby reducing HbS polymerization. In clinical trials, voxelotor increased Hb by an average of 1 g/dL, creating concern that this rise in Hb could increase viscosity, particularly when the drug was cleared. To investigate this potential rebound hyperviscosity effect, we treated SCD mice with GBT1118, a voxelotor analog, and stopped the treatment to determine the effect on blood viscosity and RBC deformability under a range of oxygen concentrations. GBT1118 treatment increased Hb, improved RBC deformability by increasing the elongation index under normoxic (EImax) and hypoxic conditions (EImin), and decreased the point of sickling (PoS) without increasing blood viscosity. The anti-sickling effects and improvement of RBC deformability balanced the effect of increased Hb such that there was no increase in blood viscosity. 48 hours after ceasing GBT1118, Hb declined from the rise induced by treatment, viscosity did not increase, and EImin remained elevated compared to control animals. Hb and PoS were not different from control animals, suggesting a return to native oxygen affinity and clearance of the drug. RBC deformability did not return to baseline, suggesting some residual rheological improvement. These data suggest that concerns regarding viscosity rise above pre-treatment levels upon sudden cessation of voxelotor are not warranted.